I Don't Want to Read This Book Aloud - Greenfield, Max, 1980-; Lowery, Mike, 1980- (New York : G.P. Putnam's Sons, 2023)
"A child shares the reasons they prefer not to read a book aloud"--.
new kids book 2023 fall.
Ages 4-8 years.
Keywords: Fear in children; Picture books; Oral reading; Books and reading -- Fiction; Fear -- Fiction; Picture books